ANALISIS IMPOR INDONESIA: Pendekatan Persamaan Simultan - Yuliadi, Imamudin (Jurnal Ekonomi & Studi Pembangunan, 2008)
To induced industrialization several raw materials and supported goods have imported to achieve economic goals. The goals of this research is to analyse some variable indeed export, terms of trade, time lag of import and exchange rate approximately have affected to import in Indonesia. Analytical method used in this research is explanatory method which is to tes hyphotesis about simultaneous relationship among variables that research, by developing the characteristics of verificative research. We used simultaneous model with two stage least square (TSLS). The result of this research shows that export, time lag of import and terms of trade have affected to importe positive and significantly. Meanwhile exchange rate have affected importÂ  negative and significantly. Otherwise terms of trade have not affected to import in Indonesia.